ON-AND OFF-FARM LABOUR ALLOCATION AMONG COOPERATIVE MEN AND WOMEN IN SOUTHERN NIGERIA - ADEYEMO, REMI (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This study is an analysis of the patterns of inter-dependence among on-farm md off-farm labour inputs of men and women cooperators. Structured questionnaires were applied by trained local enumerators to men and women cooperative farmers in Kajola, Ifedapo and Orelope local government areas. An effective sample of 400 households were available for evaluation. Results from the analysis of data show that men's off-farm labour market participation and on-farm labour inputs are inversely and positively related respectively, to farm size. In addition, there is interdependency of the on-farm labour inputs of farm men and women. There is a tendency for part-time hired workers to be substituted for on-farm labour inputs of farm women in large farm households. Major commodity produced ha substantial associations with men's and women's bours of on- and off-farm work per week.